FORMATION OF ANTS ASSEMBLAGES ON COAL MINE DUMPS - S. V. Blinova (Вестник Кемеровского государственного университета, 2015)
The dumps of opencast coal mines in Kuzbass were studies to reveal the features of natural biocenoses restoration processes. The study proved that the number of ants species increases with time, however, their density is lower than on natural biosenoses. The meadow and steppe types of ants are the first to appear on opencast coal mine dumps to be gradually replaced by the forest types. The results can be used for further development of methods of biological assessment of the extent of restoration of anthropogenically transformed ecosystems.